Study on coal water slurries prepared from coal chemical wastewater and their industrial application. (15th June 2020) - Li, Dedi; Liu, Jianzhong; Wang, Shuangni; Cheng, Jun
Highlights: CWWS is prepared using various types of coal chemical wastewater. GWW, SW, IW, and MW promote slurryability, while CW shows a negative effect. All CWWSs exhibit pseudoplastic fluid property and good stability. CMWS shows high carbon conversion rate and cold gas efficiency when being gasified. Abstract: The coal water slurry gasification combined with ammonia synthesis process produces various complex wastewaters that are difficult to handle, and the improper disposal of these wastewaters causes great harm to the environment. In this paper, coal wastewater slurry was prepared from these wastewaters, and its slurryability, rheology and stability were measured. The gasification characteristics were studied in a coal water slurry gasifier. Results show that (a) The gas washing wastewater, sulfur wastewater and industrial wastewater can promote slurryability, whereas carbonized water is not conducive to promoting slurryability. The mixed wastewater, that comprises all four types of wastewater mentioned above, promotes slurryability and has a slurry concentration of 62.0%. All coal wastewater slurries exhibit pseudoplastic fluid property, which are beneficial for industrial pumping and atomization. The stability of the samples was evaluated by analyzing the water separation rate, and all coal wastewater slurries show better stability than the coal deionized water slurry. (b) In the industrial application process, the active component of the syngas produced from the gasification of the coal mixed wastewater slurry can reach 78.6% and has a higher H2 content than the syngas produced from ordinary coal water slurry. Moreover, using the coal mixed wastewater slurry can increase cold gas efficiency by 1.57% and carbon conversion rate by 0.45% in industrial processes. Therefore, preparing and using coal mixed wastewater slurry in coal water slurry gasification combined with ammonia synthesis process not only treats high-concentration wastewater but also achieves sustainable development and a circular economy model.